Physical activity before and during the COVID-19 pandemic in Vojvodina, Serbia - Obradović, Jelena; Radulović, Nikola; Cvijović, Duško; Jurišić, Mila Vukadinović (Frontiers in Public Health, 2022)
Abstract Background: The physical activity (PA) of the youth and adult population underwent changes during the last two years due to the coronavirus (COVID-19) pandemic, and all for the purpose of maintaining the health of the population. The purpose of this study was to estimate the levels of PA in the youth population and the adult population (young and old) during the COVID-19 pandemic in the territory of Vojvodina, Serbia and to determine the differences between them. As well as, to compare this results with the results before the pandemic. Methods: A total of 1117 subjects (age 36.27 ± 15.08 years) from the Vojvodina, Serbia participated in the study. Subjects were recruited and assigned to one of three groups according to their age: youth group (N= 395; age 18 to 24 years); young adults group (N=347; from 25 to 44 years) and old adults group (N=375; age 45 to 65 years). All participants in this study completed the International Physical Activity Questionnaire Short-Form between July and November 2021, during the fourth wave of the COVID-19 pandemic. The Kruskal-Wallis test and Dunn Multiple Comparison Post-Hoc method were used for statistical analyses. Results: The youth showed the highest result in total weekly energy expenditure (3893.72 ± 2010.01 MET-min/week) compared to young adults (2528.20 ± 1804.11 MET-min/week) and old adults (2369.07 ± 2084.95 MET-min/week) during the COVID-19 pandemic in Vojvodina, Serbia. In addition, adults spent more time sitting than the youth during the same period. Furthermore, the youth achieved greater results in levels of PA during the COVID-19 pandemic compared to the situation before the COVID-19 pandemic. However, adult populations achieved lower results during the COVID-19 pandemic than before the COVID-19 pandemic. Conclusions: During the COVID-19 pandemic, the youth from Vojvodina, Serbia, achieved greater results in PA levels than the adult populations. Based on that, we recommend that it is necessary to take steps toward increasing PA in the adult population, especially old adults.